(untitled) (Advancements in Homeopathic Research, 2022)
Irritable bowel syndrome (IBS) is a common, chronic disorder that leads to decreased health-related quality of life and work productivity.Irritable bowel syndrome (IBS) is a gastrointestinal (GI) disorder characterized by altered bowel habits in association with abdominal discomfort or abdominal pain, diarrhea, constipation or a combination of both diarrhea and constipation, mucus discharge along with stools and changes in the form (appearance) of stools in the absence of detectable structural and biochemical abnormalities.Stress and emotions can strongly affect the colon. If you are feeling mentally or emotionally tense, angry or overwhelmed this can trigger colon spasms in people with IBS. These strong muscle contractions can result from mental stress because the nerves that control the normal rhythmic contractions of the colon are connected to the brain some suggestions for stress reduction are to get an adequate amount of sleep, meditation and yoga. The pathophysiology of IBS is not clear. Many theories have been put forward, but the exact cause of IBS is still uncertain. The complexity and diversity of IBS presentation makes treatment difficult. Although there are reviews and guidelines for treating IBS, they focus on the efficacy of medications for IBS symptoms there for the homoeopathic medicine is more effective in IBS if patient is treated with the individual medicine for individual patient.